PROFESIONALISME GURU DAN FAKTOR-FAKTOR YANG MEMPENGARUHINNYA - Jabar Yasir; Yuniati, Suci; Annisah Kurniati; Depriwana Rahmi (Fakultas Ilmu Tarbiyah dan Keguruan Universitas Islam Negeri Raden Fatah Palembang (UIN) Raden Fatah Palembang, 2024)
This research is a qualitative study that uses a literature review with the aim of investigating various references related to factors that influence teachers' professional competence. The research results show that the teaching profession demands meeting various professional standards. The quality of education is greatly influenced by the quality of teachers, so they are required to carry out their duties effectively. The main task of teachers is to improve the nation's overall knowledge, develop the full personality of Indonesian individuals, and create scientists and experts. However, there are still teachers who do not view teaching as a profession and therefore cannot deliver quality education, and the Indonesian government's teacher professional development program does not seem to effectively improve teachers' competencies. This paper will discuss the various issues that influence teacher professionalism.